PENGARUH TINGKAT PENDIDIKAN ORANG TUA DAN PRESTASI BELAJAR SISWA TERHADAP MINAT SISWA MELANJUTKAN STUDI KE PERGURUAN TINGGI PADA SISWA KELAS XI SMA KARTIKA 1-5 PADANG. - Putra, Suryaman; Wahyuni, Sri; Eprillison, Vivina (Pendidikan Ekonomi, 2014)
ABSTRACTÂ Â This research was conducted at Kartika High School 1-5 Padang on Effect of Parental Education and Student Achievement Students Against Interests Into College Continuing Studies In Class XI High School Students Kartika 1-5 Padang . The purpose of this study is to obtain empirical evidence about the Effect of Parental Education and Student Achievement Students Against Interests Into College Continuing Studies In Class XI High School Students Kartika 1-5 Padang . The method used in this research is descriptive and associative . This research is a symptom , events and to determine the relationship between two variables or more , where the population sampled were used as much as 123 students out of a population of 178 students . Data parental education level ( X1 ) is obtained from the results of the questionnaire or questionnaires and learning achievement ( X2 ) is obtained from documentation in the form of test scores semester academic year 2013/2014 , while the interest of the students to continue their studies to college ( Y ) is obtained from the results of questionnaire or questionnaires . Analysis of the data used in this study is a descriptive analysis and inductive analysis which consists of a normality test, multikolinielitas , heterosidasitas test , autocorrelation test , multiple regression analysis , determination ( R2 ) and test the hypothesis . The results of this study indicate that : 1 . Levels of parental education and a significant positive influence on the interests of students to continue their studies into higher education , 2 . Learning achievement and a significant positive influence on the interests of students to continue their studies into higher education , 3 . Parental level of education and achievement positive and significant effect of learning together against the interests of students to continue their studies to college . Based on these results , it is suggested that students , parents , teachers and school authorities to pay more attention to further learning achievement of children and old peoples attention in the learning process at home in an attempt to further optimize the learning achievement of students of class XI High School Students Kartika 1-5 Padang.